Pemanfaatan Aplikasi Canva Dalam Penguatan Kemampuan Literasi Digital untuk Promosi Pariwisata Berkelanjutan di Lombok Tengah - Irman Muliadi; Evita Yuniar; Muhammad Iksan; Dimas Bagus Laksono (Indonesian Journal of Education and Community Services, 2026)
The rapid advancement of digital technology necessitates enhanced digital literacy for every individual to ensure adaptability and competitiveness in the current era. This study aims to describe community empowerment efforts using the Canva application to strengthen digital literacy skills for sustainable tourism promotion in Central Lombok Regency. This research employs a mixed-methods design that combines qualitative and quantitative data. The activities were conducted as an online webinar by BAKTI KOMDIGI, in collaboration with the Founding Members of the BAKTI e-community, involving 30 participants from 17 locations with free internet access in Central Lombok. The results showed a significant increase in participants' understanding, with the average pre-test score of 33.44 ± 11.74 increasing to 88.66 ± 14.31 in the post-test. The impact evaluation indicated that respondents' digital literacy skills were in the high category (4.01), positive internet utilization was in the high category (3.93), and Canva application usage skills were in the very high category (4.22). Participants felt that Canva designs significantly helped enhance the appeal of their regional tourism promotion. This study concludes that Canva training is effective in improving community skills in producing engaging digital content. Strengthening digital literacy is expected to optimize internet infrastructure to promote local tourism potential sustainably by creating sustainable tourism content using Canva.